Does intrauterine insemination timing matter for achieving pregnancy during ovulation induction using gonadotropins? A retrospective cohort study. Issue 6 (June 2017) - Yumusak, Omer Hamid; Kahyaoglu, Serkan; Pekcan, Meryem Kuru; Isci, Esra; Cinar, Mehmet; Tasci, Yasemin
Abstract : Background : Intrauterine insemination (IUI) is a commonly used procedure to increase the infertile couples' chance of pregnancy. Single or double insemination and different timing choices are modifications of this intervention. The aim of this study was to elucidate the effect of the IUI procedure on clinical pregnancy rates when performed at 24 hours or 36 hours after ovulation triggered by human chorionic gonadotropin (hCG) following ovulation induction with gonadotropins. Methods : One hundred and thirteen women diagnosed with polycystic ovarian syndrome (PCOS) (as per Rotterdam's criteria) or unexplained infertility, who were treated using gonadotropins for ovulation induction and IUI for increasing fertilization potential, were recruited from the medical records of the infertility clinic. Demographic features, cycle outcomes, and clinical pregnancy rates of the patients were compared based on two different timing strategies of IUI (24 hours and 36 hours) following ovulation trigger using hCG. Results : Clinical pregnancy rates per cycle were 22.9% in the PCOS group and 26.9% in the unexplained group. The clinical pregnancy rates according to the timing of IUI were found to be similar for PCOS patients, unlike patients with unexplained infertility whose clinical pregnancy rates were significantly better when the IUI procedure was performed 24 hours following the hCG trigger. The cycle day of hCG trigger was also found to be significantly related to clinical pregnancy rate as utilizing a later hCG trigger day appeared to positively affect the odds of clinical pregnancy establishment. Conclusion : IUI performed at either 24 hours or 36 hours after ovulation triggered by hCG injection does not change clinical pregnancy rates for PCOS patients. Patients with unexplained infertility seem to benefit from earlier IUI procedures, which increases their fertility potential during ovulation induction with gonadotropins. Avoiding earlier than physiologically needed artificial‐hCG triggering before IUI procedures results with better pregnancy rates.